Rethinking Secular Time in Victorian England - Fisher-Høyrem, Stefan (Histories of the Sacred and Secular, 1700-2000, 2022)
This open access book draws on conceptual resources ranging from medieval scholasticism to postmodern theory to propose a new understanding of secular time and its mediation in nineteenth-century technological networks. Untethering the concept of secularity from questions of 'religion' and 'belief', it offers an innovative rethinking of the history of secularisation that will appeal to students, scholars, and everyone interested in secularity, Victorian culture, the history of technology, and the temporalities of modernity.